Basing the longitudinal distance between the bodies of the combined machine - Shirinboyev Xudoynazarbek Tolib ugli (Zien Journals, 2022)
The article presents the results of experimental studies of the influence of the longitudinal distance between the bodies of machines for preparing the soil for planting potatoes on its agrotechnical and energy indicators. Justified the longitudinal distance between the buildings
Keywords: machine; potato; soil; housing